PROBLEMS, SOLUTIONS, INTEGRATION INTO SOCIAL AND ECONOMIC LIFE OF ASYLUM SEEKERS IN MUŞ (Third Sector Social Economic Review, 2021)
The aim of the research is to reveal the problems experienced by the Syrian refugees living in Muş, their solutions, and how they can integrate into social and economic life. For this purpose, Syrian refugees were asked questions about the problems they experience in social and economic life in Muş, their solution ways, and their integration into social and economic life in Muş. The research was carried out according to the case study, which is a qualitative research method. Participants in the study consisted of 18 Syrian refugees with temporary protection status in the city centre of Muş in October 2020. Data were collected by using a structured interview form in the study. Descriptive and content analyses were used in the analysis of the data. According to the results of the research, it has been revealed that Syrian refugees have financial problems, their social cohesion is weak, and they do not have problems in communicating with other people. It can be said that ensuring the active participation of asylum seekers in social and economic life will increase social cohesion. For this reason, it can be suggested that Syrian refugees acquire different skills in public education courses, ensure that students attend school, increase job opportunities for refugees, and create opportunities for refugees to be together with other people.
Keywords: Migration; Refugee; Asylum; Integration